3D digital analysis of tooth movement with magnets and elastics in vitro. Issue 7 (July 2021) - Ishida, Yoshiki; Kuwajima, Yukinori; Ogawa, Kaho; Lee, Cliff; Da Silva, John; Emge, Jacob; Ishikawa-Nagai, Shigemi
Abstract: Objectives: Magnets have many advantages in orthodontics, and our previous studies confirmed their therapeutic potential through 3D-data analysis. The aim of this study was to compare tooth movements, including rotation, obtained via magnetic and elastic forces in crowded cases in vitro . Methods: Typodont models mimicking a crowded case were prepared. In the magnetic force-driven orthodontics (MG) group, Nd-Fe-B magnets were attached to the labial surfaces from UR4 to UL4 for attracting force, and to UR6 and UL6 for repulsing force. For the elastic force-driven orthodontic (EL) group, brackets were placed on labial surfaces from UR2 to UL2 with power-chain elastics. A NiTi archwire was used in both groups. The models were 3D scanned before and after tooth movement and exported as STL files. The pre- and post-movement STL files were superimposed. The 3D coordinates of the measurement points of the crown and root apex were obtained, and tooth displacement, 3D movements (X, Y, and Z-axis), and rotation (yaw, pitch, and roll) were calculated. Two-tailed Student's t-test was performed for comparison of the results between MG and EL groups ( n = 3). Results: Overall, both groups indicated similar movement and rotation to achieve the planned arch form. In the crown movement and rotation, no significant differences were observed between MG and EL groups. However, in the root movement, there was a significant difference between MG and EL groups in X and Z axis for the canines. Conclusions: Magnetic force-driven orthodontics demonstrated comparable results to elastics with less tipping movement, suggesting a potential future orthodontic modality. Clinical significance: This in vitro study showed the potential of magnetic force for orthodontic application. The magnetic force-driven orthodontics might provide less tipping tooth movement compared to conventional methods, such as power chains, and could be a future technique for comprehensive orthodontic treatment. Abstract : Magnets; Elastics; CAD/CAM; Orthodontics; 3D printer; 3D scanner.